Legal Protection for Consumers in the MMTC Market - Nurhayani Nst; Isma Fadhillah; Santia Devima (Journal of Legal and Cultural Analytics, 2023)
Consumer protection at this time can be separated from trading activities. It is hoped that this trading activity will create a balance of rights and obligations between business actors and consumers. The countries that are now called developed countries have gone through three levels of development. At the first level, the serious problem is how to achieve political integration to create national unity and integrity. The second level of struggle for economic and political development. Finally, at the third level, the main duty of the State is to protect the people from the negative side of industrialization. This research is descriptive (describes), analysis (describes). After the collected data is compiled, processed so that it becomes directed and systematic, start writing data related to the theme of the discussion, editing, clarifying, reducing and presenting. Using the Qualitative Method, in this method the researcher uses the perspective of the participants as a priority description in obtaining research results. Research techniques in the form of observation, experimentation, and open interviews. Buying and selling transactions require consumer protection, where the business owner must prioritize rights and obligations in consumer protection, so that the satisfaction and convenience of the transaction will run smoothly and not what is desired, where the consumer will improve even though it is not what the business actor wants